2001
DOI: 10.1111/1475-679x.00003
|View full text |Cite
|
Sign up to set email alerts
|

Do Analysts and Auditors Use Information in Accruals?

Abstract: Existing research indicates that firms with high accruals are more likely to experience future earnings problems, but that investors' expectations, as reflected in stock prices, do not appear to anticipate these problems. In this paper, we directly examine the published opinions of two types of professional investor intermediaries to see if they provide investors with information concerning the future earnings problems experienced by firms with high accruals. First, we examine the earnings forecasts of sell‐si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
456
5
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 690 publications
(521 citation statements)
references
References 16 publications
46
456
5
14
Order By: Relevance
“…On the contrary, Francis and Krishnan (1999) and Butler et al (2004) supported a negative relationship between both variables. Finally, Reynols and Francis (2000), Bradshaw et al (2001), and Johl et al (2007) observed a positive effect of company size on the probability of a receiving a qualified report.…”
Section: Opinion = F (Size Leverage Liquidity Stocks Losses Lossmentioning
confidence: 97%
See 2 more Smart Citations
“…On the contrary, Francis and Krishnan (1999) and Butler et al (2004) supported a negative relationship between both variables. Finally, Reynols and Francis (2000), Bradshaw et al (2001), and Johl et al (2007) observed a positive effect of company size on the probability of a receiving a qualified report.…”
Section: Opinion = F (Size Leverage Liquidity Stocks Losses Lossmentioning
confidence: 97%
“…Nevertheless, the available evidence is not conclusive. Although Francis and Krishnan (1999), Bartov et al (2000) and Butler et al (2004) concluded that financial leverage increased the likelihood of a qualified audit report, Bradshaw et al (2001) and Johl et al (2007) failed to report a significant relationship between financial leverage and audit qualifications.…”
Section: Opinion = F (Size Leverage Liquidity Stocks Losses Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies mentioned that investors and analysts are systematically biased in interpreting some financial accounting information (Abarbanell and Bushee 1997;Fairfield and Yohn 2001;Mendenhall 1991;Bradshaw, Richardson, and Sloan 2001;Ahmed, Nainar, and Zhou 2005). Accordingly, some studied relative comparison of the systematic biases between the two groups.…”
Section: B Studies On Relative Inefficiency Of Investors and Analystsmentioning
confidence: 99%
“…In the meantime, prior studies on finance and accounting also empirically analyzed whether analysts, who are also considered as the information intermediaries of the stock market, can effectively interpret the financial accounting information (Abarbanell and Bushee 1997;Bradshaw, Richardson, and Sloan 2001;Ahmed, Nainar, and Zhou 2005). Moreover, Weber (2009) concluded from his empirical analysis of the U.S. firms that investors properly reflect BTD under a good information environment, while analysts overly reflect BTD in future earnings forecasts.…”
Section: ⅰ Introductionmentioning
confidence: 99%